DYNAMICS OF STUDENTS’ SELF-REGULATED LEARNING WITHIN A MULTI-USER VIRTUAL ENVIRONMENT IN ECOLOGICAL LEARNING - Khalifatulloh Fiel’ardh (Jurnal Pengajaran MIPA, 2021)
This study aimed to examine the dynamics of students’ self-regulated learning within a Multi-User Virtual Environment (MUVE). Qualitative data collection and analysis were carried out within a one-group posttest-pretest design. Thirty-two students from a bilingual private school in Bandung were chosen to complete the questionnaire to measure students’ self-regulated learning and evaluate students’ conceptual understanding about ecosystem. The result showed that MUVE had an adequate impact on self-regulated learning and the conceptual understanding. The qualitative analysis provided that the most commonly used learning strategy was help-seeking. Pathway analysis showed that the self-regulated learning component significantly affects students’ conceptual understanding.